Geospatial based runoff estimation and maximum one day rainfall analysis for designing water harvesting structures - JAISWAL, SMITA; SUDHISHRI, SUSAMA; MAN SINGH1; SEHGAL, VINAY K.; MISHRA, ANIL K.; DASS, ANCHAL; SHARMA, DINESH; VENKATESH, P.; SINGH, PRASHANT; KUMAR, LOVE; MEENA, HEMRAJ (Journal of Soil and Water Conservation, 2023)
Water resources of the world in general and in India in particular are under heavy stress due to increased demand and limited availability which necessitates an urgent need to conserve as well as its judicious utilization. In this context, it becomes imperative to quantify surface runoff at watershed level for its meaningful utilization. Keeping this in view, the study is targeted towards use of the most popular and minimal data driven natural resources conservation service (NRCS) curve number (CN) method, one of the popular and widely used method to estimate the surface runoff from rainfall events using geospatial techniques. Nuh watershed of Haryana, India was selected as the study area and the daily rainfall record of 20 years (1999-2019) were used in runoff estimation. The estimated average annual runoff was found to be 119.95 mm, and the annual and monsoon runoff were found to be 18 and 13 per cent of total rainfall, respectively. The rainfall data were further analyzed to identify the best fit probability distribution and it was found that the best fit probability distribution out of 19 distributions tried for annual/monsoon, June, July, August, September and week period were Pearson 6, Gen. Extreme value, Weibull 3P, Gen. Extreme value, Log-logistic and Gen. Extreme value, respectively. For design of ponds maximum oneday rainfall of 103 mm can be taken for design at 50 years of return period. Nonetheless, the protocol described in this study can be used for design of water harvesting structures and its judicious management of stored water.